Overview of the JET ITER-like wall divertor. (August 2017) - Widdowson, A.; Alves, E.; Baron-Wiechec, A.; Barradas, N.P.; Catarino, N.; Coad, J.P.; Corregidor, V.; Garcia-Carrasco, A.; Heinola, K.; Koivuranta, S.; Krat, S.; Lahtinen, A.; et al.
Highlights: Surface analysis of the JET ITER-like wall divertor is presented for 2013–2014. Upper inner divertor remains the region of highest deposition and fuel retention. Deposition at the divertor corners is influenced by strike point location. Lifetime and erosion of tungsten coatings on JET divertor tiles are discussed. Dust and particulate generation in the divertor remains low, < 2 g. Abstract: The work presented draws on new analysis of components removed following the second JET ITER-like wall campaign 2013–14 concentrating on the upper inner divertor, inner and outer divertor corners, lifetime issues relating to tungsten coatings on JET carbon fibre composite divertor tiles and dust/particulate generation. The results show that the upper inner divertor remains the region of highest deposition in the JET-ILW. Variations in plasma configurations between the first and second campaign have altered material migration to the corners of the inner and outer divertor. Net deposition is shown to be beneficial in the sense that it reduces W coating erosion, covers small areas of exposed carbon surfaces and even encapsulates particles.